Analysis of errors in diffusion kurtosis imaging caused by slice crosstalk in simultaneous multi‐slice imaging. (6th August 2019) - Olson, Daniel V.; Nencka, Andrew S.; Arpinar, Volkan E.; Muftuler, L. Tugan
Abstract : Simultaneous multi‐slice (SMS) imaging techniques accelerate diffusion MRI data acquisition. However, slice separation is imperfect and results in residual signal leakage between the simultaneously excited slices. The resulting consistent bias may adversely affect diffusion model parameter estimation. Although this bias is usually small and might not affect the simplified diffusion tensor model significantly, higher order diffusion models such as kurtosis are likely to be more susceptible to such effects. In this work, two SMS reconstruction techniques and an alternative acquisition approach were tested to quantify the effects of slice crosstalk on diffusion kurtosis parameters. In reconstruction, two popular slice separation algorithms, slice GRAPPA and split‐slice GRAPPA, are evaluated to determine the effect of slice leakage on diffusion kurtosis metrics. For the alternative acquisition, the slice pairings were varied across diffusion weighted images such that the signal leakage does not come from the same overlapped slice for all diffusion encodings. Simulation results demonstrated the potential benefits of randomizing the slice pairings. However, various experimental factors confounded the advantages of slice pair randomization. In volunteer experiments, region‐of‐interest analyses found high metric errors with each of the SMS acquisitions and reconstructions in the brain white matter. Abstract : Residual slice leakage in simultaneous multi‐slice (SMS) imaging leads to errors in estimated diffusion kurtosis imaging (DKI) parameters. The goal of this study was to quantify these errors using two established SMS image reconstruction techniques and an alternative acquisition technique that randomized slice pairings across diffusion weighted image series. Simulations and in vivo studies demonstrated that the DKI parameter estimates were significantly altered even with a modest 2‐band SMS.